1986
DOI: 10.1128/mcb.6.9.3291
|View full text |Cite
|
Sign up to set email alerts
|

rasH mutants deficient in GTP binding.

Abstract: Single amino acid substitutions were introduced into a region of the rasH protein (residues 116, 117, and 119) homologous to a variety of diverse GTP-binding proteins. Each of the mutant p21 proteins displayed a significant reduction (10-to 5,000-fold) in GTP binding affinity. Activated rasH proteins deficient in GTP binding were unaltered in their ability to morphologically transform NIH 3T3 cells.The human ras family consists of three known genes (rasH, rasK, and rasN) which have been identified as active tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…Mutations at H-Ras codon 117 have been previously described in chemically induced liver tumors in mice (Anna et al, 1994;Stanley et al, 1994). The observed substitution disrupts a consensus sequence of Asn-Lys-X-Asp (Ras residues 116-119) commonly found in GTP-binding proteins (Der et al, 1986). This region contains the segment of the guanine nucleotide binding pocket including amino acid 117 that interacts with the guanine ring (Figure 7).…”
Section: Discussionmentioning
confidence: 87%
“…Mutations at H-Ras codon 117 have been previously described in chemically induced liver tumors in mice (Anna et al, 1994;Stanley et al, 1994). The observed substitution disrupts a consensus sequence of Asn-Lys-X-Asp (Ras residues 116-119) commonly found in GTP-binding proteins (Der et al, 1986). This region contains the segment of the guanine nucleotide binding pocket including amino acid 117 that interacts with the guanine ring (Figure 7).…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, we used the same approach to examine the possible role of a Golgi-localized Rab protein, Rab6, in the secretory and amyloidogenic processing of ␤APP. By analogy to other members of the Ras superfamily (46,47) WT or Myc-Rab6 N126I ranged from 3-to 5-fold over the endogenous Rab6, as determined by immunoblot analysis with an affinity-purified antibody against Rab6 (not shown). Expression levels of ␤APP 751 were approximately 40-fold over the endogenous ␤APP in 293 cells, so that measurements of products derived from ␤APP (i.e.…”
Section: N121imentioning
confidence: 98%
“…Although the mechanism by which v-Abl activates Ras remains unknown, it has been suggested that v-Abl can interact directly with Shc thereby initiating the formation of a complex with Grb2-mSos and ensuing Ras-Raf activation (49). A mutationally activated form of Ras, most commonly G12V, is found in up to 30% of all human tumors (53)(54)(55)(56)(57)(58)(59)(60)(61).…”
Section: Caveolin-1 Expression Inhibits Ras-mediated Transcriptional mentioning
confidence: 99%